APPROACHES TO THE SELECTION OF EXCIPIENTS FOR DENTAL GEL WITH CETYLPYRIDINIUM CHLORIDE - E. Yu. Zagorulko; A. S. Karavaeva (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2021)
The aim of the study was to determine the excipients influence on the characteristics of gels with cetylpyridinium chloride and to select the dental gel formulation gelation agents promising for the development of dental gel compositions. Hereby, the properties of the active pharmaceutical ingredient, characteristics of the specific gelation agents, as well as their influence on stability, biopharmaceutical and application properties of gels, were taken into account. Materials and methods. In this study, polymers with various gelation mechanisms were considered. Their compatibility with cetylpyridinium chloride as well as storing kinetic and colloid kinds of stability, pH of aqueous solutions, spreadability and textural properties, a penetration ability by the agar diffusion method, an osmotic activity and rheological properties of the gels, were examined. For a complex evaluation of gel compositions study results, a desirability function was used.Results. Stable homogenous dental gels with cetylpyridinium chloride can be obtained by using 25% poloxamer 407 and 5.0% high molecular weight chitosan as the basis.The addition of poloxamer 188 to high molecular weight chitosan gels can produce stable systems with improved textural characteristics as well as increase their osmotic activity. Agar and low molecular weight chitosan addition significantly decrease, whereas poloxamer188 and various molecular weight polyethyleneglycol increase the osmotic activity of 25 % poloxamer 407 gels which are also characterized by a high penetration ability.Conclusion. A complex evaluation of biopharmaceutical, physicochemical and application properties of the gels made it possible to establish that combinations of poloxamer 407 with polyvinylpyrrolidone, agar, and low molecular weight chitosan, can be recommended as a base for a dental gel with cetylpyridinium chloride.